Employees’ perceptions of symbolic corporate identity elements and employer-employee relationships at Lonmin Platinum - Lida Holtzhausen; Lynette Fourie; Annelie Naudé (Communicare, 2022)
Apart from historical and contextual factors complicating the mining industry, Lonmin Platinum’s management of employee relationships was further complicated by its diverse workforce of approximately 20 000 employees consisting of literates, semi-literates and illiterates. In addition, the company comprised five business units, each with their own corporate identity. Within this context it was expected that Lonmin’s relationship with its employees would take some strain. While the relationship between corporate image and stakeholder management has been debated, the impact of symbolic corporate identity elements on specific relationship dimensions has not yet been investigated and is addressed in this article by means of the following research question: What is the relationship between employees’ perceptions of symbolic corporate identity elements and employer-employee relationships at Lonmin Platinum? This study indicated a relationship between employees’ perceptions of how effectively the company reached it objectives, specifically a safe working environment, a healthy working environment, socio-economic empowerment and accountability, and the quality of its employee relationships.